1955
DOI: 10.1071/ar9550891
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodicity in cattle. I. Seasonal changes in coat character and their importance in heat regulation

Abstract: The seasonal changes in coat character of a control group of four young Poll Shorthorn cattle have been studied and compared with those of a similar group in which the daily photoperiod was altered to simulate the synchronous duration of daily lighting of the opposite (northern) hemisphere. Heat tolerance tests were conducted periodically as the animals assumed different coat types. The results show that the full range of coat changes which characterize well-nourished cattle of the type used in this experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1961
1961
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 0 publications
0
21
0
2
Order By: Relevance
“…Coat length and thickness are important traits linked to animal adaptation in the tropics, where longer hair is linked to animals more affected by heat stress (Yeates 1955). Silva (1998) has shown that number of hairs per unit area is important in protection of the skin against ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Coat length and thickness are important traits linked to animal adaptation in the tropics, where longer hair is linked to animals more affected by heat stress (Yeates 1955). Silva (1998) has shown that number of hairs per unit area is important in protection of the skin against ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Finch et al (1984) found that deep, woolly coats were associated with resistance to heat loss, high body temperatures, and poor performance. Clipping the coat reduced skin and rectal temperatures, as well as respiration rate, and relieved distress under extreme heat conditions (Yeates 1954(Yeates , 1955. Sleek coats have been associated with higher rates of sweating (Schleger and Bean 1971) and growth (Turner and Schleger 1960) than woolly coats.…”
Section: Cattle Coat Characteristicsmentioning
confidence: 99%
“…Heart rate was not useful as a physiological parameter in predicting heat tolerance, as it can be influenced by various environmental factors, unrelated to temperature, such as stress management caused at the time of measurement. The Santa Ines breed was separated from other breeds of animals for morphological characteristics as well for physiological characteristics and body temperatures (Figure 3) as it presented a highly pigmented epidermis, which makes the penetration of ultraviolet rays difficult as well as showing shorter hair of larger diameter and shallower hair layer thickness at the withers, T12 and rump which favors the elimination of latent heat via skin evaporation (Table 4), corroborating with YEATES (1955), who confirmed the hair length as an important characteristic related to animal adaptation in the tropics, as longer the hair the worse is the animal adaptation to heat stress. Müller (1989) also stated that the length and diameter of the hair influence the heat adaptation, since, short, smooth and thin hair provides better heat dissipation, and among the breeds with long, thick coats, the Dorper and Texel breeds had the highest values of brightness (Table 4) which favors greater absorption for solar short-wave radiation, and therefore holds greater amount of thermal energy.…”
Section: Resultsmentioning
confidence: 52%